Can dietary lipid source circadian alternation improve omega-3 deposition in rainbow trout? - Thomas Brown; David Francis; Giovanni Turchini (2010)
With the salmonid industry currently exploiting the vast majority of globally available fish oil, there is the need to optimise fish oil utilisation by increasing its efficiency in terms of transferring the health-promoting long chain omega-3 fatty acids ( n −3 LC-PUFA) into farmed fish flesh. The aim of this study was to evaluate if dietary fatty acid deposition is affected by the time of feeding, and hence identify possible innovative feeding strategies towardsmore efficient use of dietary fish oil. Over a period of 12 weeks, three diets with different lipid sources, canola oil (CO), fish oil (FO) or a 50/50 blend of the two oils (Mix), were alternated daily and fed to rainbow trout ( Oncorhynchus mykiss ). Six treatments were administered to fish, reference treatment (REF, continuously fed FO), control treatment (CT, continuously fed Mix), am canola oil ration (amCOR), pm canola oil ration (pmCOR), am canola oil satiation (amCOS) and pm canola oil satiation (pmCOS). Fish received either the CO diet in the am or pm feeds and received the FO diet at the opposite time. A significant increase in growth and feed consumption was noted in the pmCOS treatment. Fillet fatty acid profile was modified by associated feeding schedules and was generally reflective of dietary fatty acid profile. No significant increases in n −3 LCPUFA deposition were observed. However, both linoleic acid (18:2 n −6) and α-linolenic acid (18:3 n −3) contents were significantly higher in pmCOR compared to amCOR and CT. The results of the present study suggest the existence of cyclical circadian patterns in fatty acid deposition in rainbow trout.